Spatio-temporal variation in rate of carbonate deposition by encrusting organisms in different reef microhabitats from Eastern Pacific coral reefs. (5th August 2019) - Alvarado-Rodríguez, J. F.; Nava, H.; Carballo, J. L.
Abstract: Reef encrusting calcifiers (non-scleractinian species) constitute assemblages that participate in the carbon cycle at coral reefs. Despite their apparent secondary role in building the reef framework, they contribute to the reef consolidation binding sediments and inducing larval recruitment from other epilithic invertebrates. The contribution of encrusting calcifiers on reef accretion was examined by the assessment of their rate of carbonate deposition on four different simulated reef microhabitats using calcification accretion units (CAUs) during 12 months at Playa Las Gatas and Islote Zacatoso, two coral communities from the coast of the Mexican Pacific. Encrusting calcifiers from Playa Las Gatas, the most impacted site, showed a rate of carbonate deposition (mean ± SD) four times higher than at Islote Zacatoso (10.02 ± 3.22 g CaCO3 m −2 d −1 vs 2.48 ± 1.01 g CaCO3 m −2 d −1 ). Overall, the rate of carbonate deposition on surfaces protected from sedimentation and light was up to 1.8 times higher than on exposed ones (11.40 ± 4.35 g CaCO3 m −2 d −1 vs 6.18 ± 3.13 g CaCO3 m −2 d −1 ). Carbonate deposition by calcareous algae was higher on the well-lit exposed surfaces while filter-feeding invertebrates showed the major contribution on the shaded cryptic surfaces. Although rate of carbonate deposition by encrusting calcifiers seems to be lower than hermatypic corals, it seems to be relevant on coral reefs affected by anthropogenic impacts where coral calcification is low. Under global demise of coral reefs by environmental degradation and climate change, encrusting calcifiers may become relevant for the process of carbonate deposition.